Acral pseudolymphomatous angiokeratoma: case report and literature review - Priscila Pacheco Lessa; Juliana Chaib Ferreira Jorge; Flávia Regina Ferreira; Marcia Lanzoni de Alvarenga Lira; Samuel Henrique Mandelbaum (Sociedade Brasileira de Dermatologia, 2013)
The authors describe a case of a female patient with Acral Pseudolymphomatous Angiokeratoma of Children, known as APACHE. It is a rare benign cutaneous disease, of unknown etiology, characterized by multiple, asymptomatic erythematous-violaceous papules and nodules, usually located unilaterally with acral distribution. Today, this denomination is questionable, since there are published reports of this disease in adults and in different locations. Clinically, it is similar to an angiokeratoma, whereas hystologically, it corresponds to a distinct type of pseudolymphoma. The immunohistochemical study is required to distinguish APACHE from cutaneous lymphoma.